Dosage Forms Innovation and Future Perspectives - Ahmad, Usama (IntechOpen, 2023)
Dosage forms are pharmaceutical formulation products in the form in which they are presented in the market. They are a crucial component of contemporary pharmaceutical research. The field of dosage forms is large and diverse and includes everything from conventional solid and liquid dosage forms to more recent innovations like nanoparticles and gene therapy. This book provides a comprehensive overview of dosage forms, including their formulation and development. Chapters address such topics as novel dosage forms in ophthalmic applications, orally disintegrating tablets, layered tablets, pharmacokinetics and pharmacogenomics, and much more.